DNMT1-mediated regulation of somatostatin-positive interneuron migration impacts cortical architecture and function - Julia Reichard; Philip Wolff; Song Xie; Ke Zuo; Camila L. Fullio; Jian Du; Severin Graff; Jenice Linde; Can Bora Yildiz; Georg Pitschelatow; Gerion Nabbefeld; Lilli Dorp; et al. (Nature Communications)
Abstract The coordinated development of cortical circuits composed of excitatory and inhibitory neurons is critical for proper brain function, and disruptions are linked to a spectrum of neuropsychiatric disorders. While excitatory neurons are generated locally in the cortical proliferative zones, inhibitory cortical interneurons (cINs) originate in the basal telencephalon and migrate tangentially into the cortex. Here, we show that DNA methyltransferase 1 (DNMT1) is essential for the migration and integration of somatostatin (SST)-expressing interneurons in mice. Dnmt1 deletion causes premature exit of SST+ cINs from the superficial migratory stream and alters the expression of key developmental genes. Unexpectedly, Dnmt1-deficient SST+ interneurons also exert non-cell-autonomous effects on cortical progenitor cells, resulting in subtle yet lasting alterations in cortical layering. These findings propose a role for DNMT1 in governing the migration of SST+ interneurons and mediating their instructive signaling to cortical progenitor cells, thereby shaping cortical architecture and influencing long-term network function.